2017
DOI: 10.2215/cjn.01470217
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review for Strategies to Increase Living Kidney Donation

Abstract: We identified an important gap in the literature for evidence-based strategies to increase living kidney donation. From the limited data available, strategies directed at potential recipients and their social networks are the most promising. These results can inform transplant programs that are considering strategies to increase living kidney donation and highlight the need for conduct of high-quality study to increase living donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 45 publications
0
55
0
1
Order By: Relevance
“…Many programs have been designed and implemented to assist transplant candidates to identify a living donor successfully . Explore Transplant is one such program .…”
Section: Discussionmentioning
confidence: 99%
“…Many programs have been designed and implemented to assist transplant candidates to identify a living donor successfully . Explore Transplant is one such program .…”
Section: Discussionmentioning
confidence: 99%
“…This highlights that in most countries information from the treating physicians is more important than from the World Wide Web. A scoping review addressed strategies to increase live kidney donation and found that recipient-based education that reaches friends and family has the best evidence of being effective [32]. In contrast to the global trend, the Google Trends TM search highlighted an increase in search queries in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Several other strategies show promise in increasing access to living donor kidney transplantation whereas other strategies do not (summarized in a review by Barnieh et al [34]). These strategies involve complex processes and include greater education for patients with kidney failure, removing disincentives (such as the expenses incurred by donors), a web-based system for donor-candidate screening, use of transplant champions to help intended recipients prepare for kidney transplantation (including finding living kidney donors), and creating dedicated multidisciplinary healthcare teams to support living kidney donation (34,35). Rigorous research methods are needed to assess the effects of complex interventions (36).…”
Section: Solutions To Improve Patient Experiences and Safely Increasementioning
confidence: 99%